Adaptive Policy Model in Poverty Alleviation in Indonesia - Anggraini, Dian; KGS. M.Sobri; Andries Lionardo; Raniasa Putra (MIMBAR : Jurnal Sosial dan Pembangunan, 2025)
Abstract. Poverty is one of the main problems of Sustainable Development (SDGs) which is characterized by the large number of poor people, unemployment, backwardness, and depression. The high number of poor people causes a decrease in human resources, adaptive policies are needed which are considered as important solutions in overcoming the problem of poverty. The theory used was put forward by Swanson who stated that the purpose of adaptive policies is to anticipate a series of conditions that exist in the future through a strong initial design using integrated and forward-looking analysis, multi-stakeholder deliberation and can monitor possible adjustments to situations that can be anticipated. The purpose of this study is to analyze the appropriate adaptive policy model in overcoming poverty in Indonesia. This study uses a qualitative approach with a literature review data collection method. The results of study This mention that policy model development countermeasures poverty should made adaptive , flexible , responsive , and participatory . Recommendations general emphasize strengthening institutions , coordination , participation society , and utilization of data and technology .